2014
DOI: 10.1364/oe.22.026265
|View full text |Cite
|
Sign up to set email alerts
|

Modified shifted angular spectrum method for numerical propagation at reduced spatial sampling rates

Abstract: The shifted angular spectrum method allows a reduction of the number of samples required for numerical off-axis propagation of scalar wave fields. In this work, a modification of the shifted angular spectrum method is presented. It allows a further reduction of the spatial sampling rate for certain wave fields. We calculate the benefit of this method for spherical waves. Additionally, a working implementation is presented showing the example of a spherical wave propagating through a circular aperture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Ritter [19] developed an AS method for off-axis field calculations with a reduced sampling frequency that is restricted to band-limited fields propagating in off-axis direction. Hillenbrand et al [20] proposed a tile summation for AS for focused field calculations with reduced sample size.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ritter [19] developed an AS method for off-axis field calculations with a reduced sampling frequency that is restricted to band-limited fields propagating in off-axis direction. Hillenbrand et al [20] proposed a tile summation for AS for focused field calculations with reduced sample size.…”
mentioning
confidence: 99%
“…Shimobaba and co-workers [16,17] developed scaled AS employing a nonuniform Fourier Transform, and Yu et al [18] proposed an approach based on the chirped z-transform. Ritter [19] developed an AS method for off-axis field calculations with a reduced sampling frequency that is restricted to band-limited fields propagating in off-axis direction. Hillenbrand et al [20] proposed a tile summation for AS for focused field calculations with reduced sample size.…”
mentioning
confidence: 99%
“…Hence, (14) can be equivalently expressed as a 2D aperiodic convolution of the complex amplitude a with the kernel p x3 ( · )e −j( · ) Tkin , followed by a modulation in the space domain. This approach is called tilt transfer because the shift of y in in the Fourier domain is transferred to the propagation kernel [37,38]. The advantage of this formulation is that, by contrast to y in , the complex amplitude a is not far from a constant signal, up to some noise and optical aberrations.…”
Section: Computation Of the 3d Incident Field: U Inmentioning
confidence: 99%
“…The structure of a mini-camera is such that the beam propagation is divided into three general processes based on their different propagation models. We derived the light-field distribution of the reflection on the screen through a detailed analysis of the model as well as a calculation using the angular spectrum method (ASM) [6] and the combined aperture method [4]. Based on the theoretical model, we found that the experimental results were in agreement with the corresponding simulation results with little error.…”
Section: Introductionmentioning
confidence: 98%